Assessment of schoolchildren functional shifts in a polluted air - Nugumanova, Sh.M.; Оleshchenko, А.М.; Prozhenik, A.G. (Fundamental and Experimental Biology, 2016)
Environmental pollution has an adverse effect on the functional state of the body of the child population. Exposure to environmental factors leads to the development of negative effects in the health status of the population, which translates into an increase in the incidence and deterioration of physical development. The unfavorable environment adversely affects the level of physical development and functional state in children, causing a high level of functional tension. The process of adaptation of schoolchildren living in different ecological zones of well-being, accompanied by a decrease in performance. Functional stress in children living in contaminated areas in line with the levels of pronounced stress and overexertion. The incidence of school-children living in areas contaminated area reflected the reduced level of resistance of the body and testified about the negative impact neblagorpiyatnyh factors on the adaptive activity of the organism adolescents.